Pengaruh Status Sosial Ekonomi Orang Tua dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa IKIP Budi Utomo Malang - Herlina Herlina; Putri Vina Sefaverdiana; Melisa Wahyu Fandyansari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Students are required to keep up with the times, a person tends to consume behavior that is just a desire, not a need. Supported by high socio-economic status of parents, which will then support a person's lifestyle that makes a person lead to consumptive behavior. The research method used is quantitative, the research instrument is with a likret scale, data collection techniques are questionnaires and documentation and data analysis techniques are using t and f tests. The results of the discussion (1) The influence of parents' socioeconomic status on consumptive behavior obtained a significance value of 0.002 <0.05, so partially there is a positive and significant influence, (2) The influence of lifestyle on consumptive behavior obtained a significance value of 0.001 <0.05, so partially there is a significant positive effect, (3) Simultaneous testing based on the results of the variable test of parents' socioeconomic status, lifestyle, has a significant effect on consumptive patterns with a value of F = 777, sig. = 0.004 <0.05 then Ho is rejected and Ha is accepted. <0.05 then Ho is rejected and Ha is accepted.